Mobility as a Service: Development scenarios and implications for public transport. (September 2018) - Smith, Göran; Sochor, Jana; Karlsson, I.C. MariAnne
Abstract: Bundled offerings that facilitate using multiple means for solving everyday travel needs are proposed to hold potential to facilitate a modal shift from private cars to servitized transport modes, including public transport (PT). This type of offering, often coined Mobility as a Service (MaaS), may require new forms of partnerships, in which private actors play a larger role in the creation of public value. Accordingly, based on input from 19 interviews with MaaS actors active in West Sweden, this paper explores how MaaS could develop and how PT might be affected. Three predictive scenarios are identified – market-driven, public-controlled and public-private – and the implications for future PT, in terms of the scope, usage, access, business model, competence structure and brand value, are discussed in relation to these. The authors conclude that finding a regulatory 'sweet spot' that drives innovation and secures public benefits will be key for future developments.